Simulation of 125I Auger emission spectrum with new atomic parameters from MCDHF calculations. (January 2022) - Sampaio, J.M.; Ekman, J.; Tee, B.P.E.; du Rietz, R.; Lee, B.Q.; Pires, M.S.; Jönsson, P.; Kibédi, T.; Vos, M.; Stuchbery, A.E.; Marques, J.P.
Highlights: New 125 I atomic decay emission data from MCDHF calculations are presented. Simulated Auger electron emission spectra using the new data and the EADL are compared with experiment. Dose point kernels are simulated with Geant4 using the new atomic data and compared with those obtained from EADL. Abstract: New 125 I atomic decay emission data of medical interest are presented. The calculations are based on two atomic structure codes that implement the multi-configuration Dirac-Hartree-Fock method. Radiative and non-radiative ransition rates are calculated in this method and then used to generate the atomic deexcitation cascade. Subshell transition rates, level widths and fluorescence yields are compared to the Evaluated Atomic Data Library. Coster-Kronig and Auger electron emission yields are also compared with results from other authors. The comparison with the experimental electron emission spectrum shows that the new calculations can reproduce very well the structure of the K-LL Auger electron peaks and improve the description of the M Auger peaks below 300 eV. The 125 I dose-point kernel is also simulated using the new data, resulting in higher values below 10 nm when compared those obtained with the Evaluated Atomic Data Library.